Photo sensor based on 2D materials - Late, Dattatray J.; Bhat, Anha; Rout, Chandra Sekhar (Fundamentals and Sensing Applications of 2D Materials, 2019)
This chapter starts with a general introduction to the interaction of light with matter and use of this principle for sensing. Photo-sensing devices based on two-dimensional (2D) materials are compared to conventional designs and their respective differences discussed in detail. A range of 2D materials are introduced with a generic comparison based on their individual properties and importance to the generation of a photoresponse. Besides transition-metal dichalcogenides, the chapter also deals with black phosphorous photosensor devices. Different heterostructure architectures based on 2D layered structures are investigated and their role in next generation optoelectronics is discussed.